QEMSCAN® automated mineralogical analysis of PM2.5 and PM4: A preliminary study of underground coal mine dust from Poland and Slovenia - Johnson, Diane; Rollinson, Gavyn. K.; Arif, Ali Talib; Moreno, Teresa; Ruiz, Pedro Trechera; Lah, Robert; Lubosik, Zbigniew; Pindel, Thomas; Gminsk, Richard; Williamson, Ben J. (Frontiers in Earth Science, 2022)
This study reports the first successful QEMSCAN® automated mineralogical analysis of physically size separated, potentially toxic PM4 and PM2.5 from deep coal mines in Poland and Slovenia. QEMSCAN® was setup to automatically delimit 100,000 ‘particles’ per sample based on their scanning electron microscope (SEM)-backscattered electron (BSE) signal, subject these to X-ray elemental point analysis in a grid pattern (0.5 µm spacing), assign a mineral name to each point of analysis and then output the results as particle size, shape, mineralogy and mineral associations data and as mineral/phase maps. The dusts were prepared as dispersions on a polyethylene sheet so that coal particles, with a slightly higher BSE signal, could be recognized from their substrate. Samples were analyzed repeatedly and in different orientations to determine the effects of sample geometry and topography. QEMSCAN® mineral identifications were manually checked using standard SEM X-ray elemental analysis. From the pilot study analyses of Polish and Slovenian coal dust samples, they contain varying proportions of coal, quartz and other silicates, sulphides, sulphates, carbonates, oxides and other minerals, and notable concentrations of fly-ash particles, which highlights the need for larger scale and wider ranging studies. The further potential of the newly developed QEMSCAN® methodology is discussed.